Children admitted to Paediatric Intensive Care at Red Cross War Memorial Children?s Hospital with Non-Accidental injuries (2012-2020): a retrospective descriptive study - Bowes, Lynelle (Department of Paediatrics and Child Health, 2025)
Objectives: To describe the characteristics and outcomes of patients admitted to the paediatric intensive care unit (PICU) with suspected non-accidental injury (NAI). Methods: A retrospective descriptive study of routinely collected data from all children admitted to the PICU with suspected NAI from 1 January 2012 to 31 December 2020. Results: Of 11345 children admitted to PICU, 42 (0.4%) patients with suspected NAI (median (IQR) age 20.3 (7.9 – 62.6) months; 61.9% male) were included in the data analysis. Most patients sustained physical injury (n=31; 73.8%) from assaults (n=19; 45.2%), and head injuries were the most common injury site (n=24; 57.1%). Of the patients, 37 (88.1%) received invasive mechanical ventilation for median 2.0 (IQR) (1.0 – 3.8) days. PICU mortality was 28.6% (n=12), with a risk adjusted mortality (observed/mean predicted mortality) of 3.2. Of the 30 PICU survivors, 7 (23.3%) were discharged with long-term disability, whilst the functional outcome of 16 (53.3%) survivors is not known. A multivariable binary logistic regression was conducted to determine the effect of inotropes, type of NAI, mechanism of injury, injury site (head, skin – eye injuries removed from the model for reasons of collinearity), and multiple injuries on patient survival. The model was significant (p = 0.001) and a good fit for the data (Nagelkerke R square 0.78) and was able to correctly predict 85.7% of cases. None of the variables in the model were r found to be independently associated with survival (p > 0.1 for all). Conclusions: Children who have sustained NAI represent a small proportion of PICU admissions, with higher-than-expected mortality and considerable morbidity. Patient follow-up is recommended to determine long-term functional and psychosocial outcomes.